Optimization of diamond-like carbon coatings for mechanical and tribological applications. Review - Reshetnyak, E.N.; Luchaninov, A.A.; Strel’nitskij, V.E. (Problems of Atomic Science and Technology, 2023)
Diamond-like carbon (DLC) coatings are used to improve the quality of industrial products due to a wide range of exceptional physical, mechanical and tribological properties. Problems that limit the scope of application of hard non-hydrogenated DLC coatings with properties closest to those of diamond are considered. The scientific literature is reviewed devoted to improving the characteristics of DLC-based wear-resistant coatings. The approaches currently used to reduce internal compressive stresses, improve adhesion to the substrate, and increase the strength of coatings are analyzed. Aspects of optimization of deposition parameters, doping, constructing the gradient and multilayer structure are considered. Based on the generalization of the results of the reviewed publications, a conclusion is made about the advantages of using coatings with a multilayer structure. A promising design undoped multilayer DLC coatings with high protective properties is discussed. Алмазоподібні вуглецеві покриття використовуються для підвищення якості промислових виробів завдяки широкому спектру виняткових фізичних, механічних і трибологічних властивостей. Розглянуто проблеми, що обмежують сферу застосування твердих негідрогенізованих алмазоподібних покриттів із властивостями, які найбільш близькі до алмазу. Проведено огляд наукової літератури, що присвячена покращенню характеристик зносостійких покриттів на основі алмазоподібного вуглецю. Проаналізовано сучасні підходи до зниження внутрішніх напружень стиску, покращення адгезії до основи та підвищення міцності покриттів. Розглянуто аспекти оптимізації параметрів осадження, легування, побудови градієнтної та багатошарової структури. На основі узагальнення результатів розглянутих публікацій зроблено висновок про переваги використання покриттів із багатошаровою структурою. Розглядається перспективна конструкція нелегованих багатошарових DLC-покриттів з високими захисними властивостями.